ANALYSIS POSITIONING OF NOTEBOOK PRODUCED BY HEWLETT PACKARD (HP) IN BALI PROVINCE - Sri Ariyani, Ni Wayan; Sukaatmadja, I Putu Gde; Rimbawan, Nym Dayuh (Jurnal Teknologi Elektro; Vol 8 No 2 (2009): JURNAL TEKNOLOGI ELEKTRO, 2012)
Nowadays notebook is not a luxurious thing any more, but has been one of  the things that should be obligatorily owned by high school student, university student, and practitioners. The competition among the notebooks has been getting tight. The reason is that they have been produced with almost similar attributes, qualities, and design but different prices. This study aims at (1) identifying the similarity between the notebook produced by Hewlett Packard ( hp ) and those produced by its competitors such as, IBM, Sony, Acer and Toshiba, (2) identifying the consumers perception of the notebook produced by Hewlett Packard ( hp ) and of those produced by its competitors, (3) identifying what is the superiority of the notebook produced by Hewlett Packard ( hp ) compared with the superiority of those produced by its competitors, and (4) identifying what strategy is relevant in strengthening the positioning of the notebook produced by Hewlett Packard ( hp ). The samples were determined by purposive sampling, and the respondents employed totaled 100 spreading over Denpasar City. To achieve maximum result, Multi Dimensional Scaling (MDS) was applied as the instrument of analysis to identify the similarity among the notebooks and Correspondence Analysis (CA) was employed as the instrument of analysis to identify the superiority of each variable of every notebook. The result of the study show that the notebook produced by Hewlett Packard ( hp ) is perceived to resemble those produced by IBM, Sony, and Toshiba. This means that the notebook produced by Hewlett Packard ( hp ) competes against those produced by IBM, Sony, and Toshiba, and that it does not compete against that produced by Acer. The notebook produced by Hewlett Packard ( hp ) is superior in the variables of product varieties, post sales, distribution channels, and promotion. The notebook produced by IBM superior in the variable product quality, while that produced by Sony is superior in the variable of product  design, that produced by Toshiba is superior in the variable of  brand image, and that produced by Acer is superior in the variable of price. To strengthen the positioning of the notebook produced by Hewlett Packard ( hp ), the relevant strategy is perpetually differentiating the product, maintaining the superior variable by creating new varieties, continuously improving the post sales service to every customer, expanding the distribution channels to the regencies, and keeping increasing promotion.